A solid electrolyte and its preparation method and application

By coating the tin dihalide SnX2 layer on the surface of the sulfide solid electrolyte, the interfacial side reaction problem of the sulfide electrolyte when hydrolyzing in humid air and contacting lithium metal is solved, and the stability of the electrolyte and the cycling performance of the battery are significantly improved.

CN119361809BActive Publication Date: 2025-05-02ZHUJI PAWA NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411897744.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-05-02
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The sulfide solid electrolyte is easily hydrolyzed in humid air, resulting in a decrease in ionic conductivity and interfacial side reactions will occur when in contact with lithium metal, affecting battery performance.

Method used

SnX2 dihalide is used as a cladding layer to coat part of the surface of the sulfide solid electrolyte. By blocking the contact between water and oxygen, the growth of lithium dendrites is reduced and the interfacial side reaction is inhibited, thereby improving electrochemical performance.

Benefits of technology

It improves the stability and ion conduction performance of sulfide solid electrolytes, enhances the cycle stability and thermal stability of the battery, and improves the overall electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361809B_ABST
    Figure CN119361809B_ABST
Patent Text Reader

Abstract

The present invention discloses a solid electrolyte, its preparation method and application, which includes a sulfide solid electrolyte and a coating layer coated on at least part of the surface of the sulfide solid electrolyte; wherein: the coating layer is a tin dihalide SnX2 material, and X is one or more of F, Cl, Br, and I. The solid electrolyte in the present invention uses tin dihalide SnX2 as the coating layer, which can block the contact between the sulfide solid electrolyte and water and oxygen, and improve its stability in air. In addition, the tin element in tin dihalide SnX2 can reduce the direct contact between the sulfide solid electrolyte and the electrode, inhibit the occurrence of interfacial side reactions, thereby improving the ionic conductivity and chemical stability, and being more conducive to ion transport. The halogen elements in tin dihalide SnX2 will react with the lithium negative electrode to generate LiX (such as lithium fluoride), which can form a relatively stable solid electrolyte interface film (SEI film) on the surface of the lithium negative electrode, thereby improving the cycle stability and ionic conductivity of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state batteries, and specifically relates to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] In recent years, the energy demand for chemical power sources in electric vehicles, mobile electronic devices and large energy storage devices has continued to grow, and there is a greater demand for batteries with higher capacity, faster charging and more stable cycle stability, which has also promoted the rapid development of all-solid-state lithium battery technology. All-solid-state lithium-ion batteries have safety characteristics that liquid batteries cannot match because they do not use flammable components such as organic electrolytes in their systems. In addition, solid-state electrolytes can inhibit the growth of lithium dendrites, making the practical application of metal lithium negative electrodes possible.

[0003] So far, a lot of research has been done on solid electrolyte membranes, especially the relevant research on sulfide solid electrolyte membranes and oxide solid electrolyte membranes is more mature. Among them, sulfide solid electrolytes have excellent mechanical properties, and their ionic conductivity can reach a level comparable to that of liquid electrolytes. Therefore, they are considered to be one of the solid electrolyte materials with broad application prospects. However, there are still some problems in the actual use of sulfide electrolytes. For example, sulfide solid electrolytes are very easy to hydrolyze in humid air, which will lead to a decrease in the ionic conductivity of the electrolyte, greatly limiting the application and production of sulfide solid electrolytes; for example, when sulfide solid electrolytes come into contact with lithium metal, serious interfacial side reactions will occur, causing the battery interface impedance to increase, affecting the performance of all-solid-state batteries. Therefore, further improving sulfide solid electrolytes is very necessary to promote the development of all-solid-state batteries. Summary of the invention

[0004] The purpose of the present invention is to provide a solid electrolyte and a preparation method and application thereof, so as to further improve the electrochemical performance of the solid electrolyte.

[0005] In a first aspect, the present invention provides a solid electrolyte, which adopts the following technical solution:

[0006] A solid electrolyte comprises a sulfide solid electrolyte and a coating layer coated on at least a portion of the surface of the sulfide solid electrolyte; wherein the coating layer is tin dihalide SnX2, and X is one or more of F, Cl, Br, and I.

[0007] Preferably, the mass of the coating layer is 1-10 wt % of the mass of the sulfide solid electrolyte.

[0008] Preferably, the sulfide solid electrolyte is Li3PS4, Li7P3S 11 , Li 10 GeP2S 12, Li 10 SiP2S 12 One of them.

[0009] In a second aspect, the present invention provides a method for preparing a solid electrolyte, comprising the following steps:

[0010] In an inert atmosphere, tin dihalide SnX2 is ultrasonically dispersed in solvent 1 to obtain a coating agent dispersion; in an inert atmosphere, a sulfide solid electrolyte is added to solvent 2, heated and stirred to obtain an electrolyte slurry; the coating agent dispersion is added to the electrolyte slurry, stirred and mixed, heated and evaporated, and then further dried to obtain a solid electrolyte.

[0011] Preferably, the solvent 1 is ether; the concentration of tin dihalide SnX2 in solvent 1 is 0.02~0.4 g / mL; solvent 2 is dimethyl sulfoxide; the concentration of sulfide solid electrolyte in solvent 2 is 0.4~0.7 g / mL; the coating agent dispersion and the electrolyte slurry are mixed in a ratio in which the mass of tin dihalide SnX2 is 1~10wt% of the mass of the sulfide solid electrolyte.

[0012] Preferably, the ultrasonic dispersion time is 4 to 6 hours; the inert atmosphere is argon atmosphere; the heating and stirring temperature is 95 to 105°C, the heating and stirring speed is 1200 to 1600 rpm, and the heating and stirring time is 5 to 8 hours; the stirring and mixing speed is 1200 to 1600 rpm, and the stirring and mixing time is 2 to 5 hours; and the drying temperature is 180 to 220°C.

[0013] Preferably, the method for preparing the sulfide solid electrolyte comprises the following steps:

[0014] S1: Calculate the amount and proportion of raw materials according to the structural formula of sulfide solid electrolyte;

[0015] S2: Calculate the filling volume of ball mill beads according to formula (1) and the volume of the ball mill jar; then add the corresponding volume of large ball mill beads into the ball mill jar to fill it to the calculated filling volume, and then add small ball mill beads to fill the gaps between the large ball mill beads;

[0016] Formula (1) is:

[0017] S3: Under an inert atmosphere, raw materials are added to a ball mill jar containing ball mill beads, followed by ball milling. After the ball milling is completed, the raw materials are sieved to obtain a sulfide solid electrolyte.

[0018] Preferably, in step S1, the raw materials include Li2S and P2S5; when the sulfide solid electrolyte contains Ge, the raw materials also include GeS2; when the sulfide solid electrolyte contains Si, the raw materials also include SiS2.

[0019] Preferably, in step S2, the diameter of the large ball milling beads is 10 mm, and the diameter of the small ball milling beads is 1-2 mm; the number of the small ball milling beads is 1 / 3-2 / 3 of the number of the large ball milling beads.

[0020] Preferably, in step S3, the ball milling process is specifically as follows: first, preliminarily mix at 400-500 rpm for 10-20 min; then, ball mill at 1200-1600 rpm for 3-4.5 h; and finally, ball mill at 2000-2200 rpm for 30-45 min.

[0021] In the present invention, the step-by-step solid phase process with different low, medium and high rotation numbers of ball milling beads can reduce the energy consumption of preparing sulfide solid electrolytes and improve the production efficiency of sulfide solid electrolytes.

[0022] In a third aspect, the present invention provides an all-solid-state battery, the electrolyte of which adopts the aforementioned solid electrolyte.

[0023] Beneficial effects of the present invention:

[0024] The solid electrolyte of the present invention uses tin dihalide SnX2 as a coating layer, which can block the contact between the sulfide solid electrolyte and water and oxygen, and improve its stability in the air. In addition, the tin element in tin dihalide SnX2 can reduce the direct contact between the sulfide solid electrolyte and the electrode, inhibit the occurrence of interface side reactions, thereby improving the ion conductivity and chemical stability, and is more conducive to ion transmission. The halogen elements in tin dihalide SnX2 will react with the lithium negative electrode to generate LiX (such as lithium fluoride), which can form a relatively stable solid electrolyte interface film (SEI film) on the surface of the lithium negative electrode, thereby improving the cycle stability and ion conductivity of the battery. Furthermore, tin dihalide also has good thermal stability and air stability. When it is used as a coating layer of the sulfide solid electrolyte, the comprehensive performance of the solid electrolyte can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The cycle performance diagram of the solid-state battery assembled with the solid electrolytes prepared in Examples 1 to 3 and Comparative Example 1.

[0026] Figure 2 The cycle performance diagram of the solid-state battery assembled with the solid electrolyte prepared in Examples 4 to 6. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0030] The calculation formula of ball mill filling volume in the embodiment is as follows:

[0031]

[0032] Among them: A 孔隙率 0~0.15, φ 介质填充比 is 0.3.

[0033] The bead filling volume indicates the volume filled to a given volume by the beads added; it is not the sum of the actual volumes of all the beads.

[0034] Example 1

[0035] The solid electrolyte in this embodiment consists of a Li3PS4 electrolyte and a SnF2 coating layer coated on the surface of the Li3PS4 electrolyte.

[0036] The specific preparation method is as follows:

[0037] S1: Ball milling preparation of Li3PS4

[0038] S1-1: According to the structural formula of Li3PS4, Li2S and P2S5 are evenly mixed in a molar ratio of 3:1, wherein the amount of Li2S powder (7.66 g, 99.98%) and P2S5 powder (12.34 g, 99%) required to prepare 20 g of the required sulfide solid electrolyte is calculated.

[0039] S1-2: The volume of the ball mill is 125 mL. The filling volume of the ball mill is 37.5 mL according to the calculation formula (1). Add 10 mm ball mills to the ball mill until it is filled to 37.5 mL. Then add 1 mm ball mills to fill the gaps between the 10 mm ball mills. The ratio of the number of 10 mm ball mills to the number of 1 mm ball mills is 3:2.

[0040] S1-3: In an inert argon atmosphere in a glove box, Li2S powder and P2S5 powder were added to a ball mill at a ball-to-material ratio of 15:1. First, they were mixed at 500 rpm for 15 min; then, they were ball-milled at 1450 rpm for 4 h; then, they were ball-milled at 2100 rpm for 40 min. After the ball mill material was cooled, the ball mill beads were filtered out through a 200-mesh sieve, and then through a 400-mesh sieve to obtain Li3PS4.

[0041] S2: Preparation of solid electrolyte

[0042] S2-1: In an inert argon atmosphere in a glove box, add 0.2 g of SnF2 to 5 mL of ether solvent and disperse by ultrasonic at room temperature for 5 h to obtain a dispersion.

[0043] S2-2: In an inert argon atmosphere in a glove box, add 20 g of the Li3PS4 powder prepared in step S1 to 35 mL of dimethyl sulfoxide, stir at 100°C and 1500 rpm for 6 h, and after stirring, cool to room temperature to obtain a viscous electrolyte slurry.

[0044] S2-3: Add the dispersion prepared in step S2-1 to the viscous electrolyte slurry prepared in step S2-2, and then stir at 1500 rpm for 3 hours to obtain a mixed slurry. After heating and evaporating the mixed slurry, place it in an oven at 200°C for further drying to obtain a powder. The powder is sieved through a 200-mesh sieve to obtain a solid electrolyte.

[0045] Comparative Example 1

[0046] Compared with Example 1, no coating is performed, that is, there is no step S2; the corresponding solid electrolyte is Li3PS4.

[0047] Example 2

[0048] It is basically the same as Example 1, except that in step S2-1, the amount of SnF2 added is 1 g.

[0049] Example 3

[0050] Basically the same as Example 1, except that in step S2-1, the amount of SnF2 added is 1.6 g.

[0051] Example 4

[0052] Compared with Example 2, the difference is that SnF2 in step 2-1 is replaced by SnCl2.

[0053] Example 5

[0054] Compared with Example 2, the difference is that SnF2 in step 2-1 is replaced by SnBr2.

[0055] Example 6

[0056] Compared with Example 2, the difference is that SnF2 in step 2-1 is replaced by SnI2.

[0057] Example 7

[0058] The solid electrolyte in this embodiment is composed of Li7P3S 11 Electrolyte and coating on Li7P3S 11 The SnF2 coating on the electrolyte surface.

[0059] The specific preparation method is as follows:

[0060] S1: Preparation of Li7P3S by ball milling 11

[0061] S1-1: According to Li7P3S 11 According to the structural formula, Li2S and P2S5 are evenly mixed in a molar ratio of 7:3, wherein the amounts of Li2S powder (6.52 g, 99.98%) and P2S5 powder (13.48 g, 99%) required to prepare 20 g of the required sulfide solid electrolyte are calculated.

[0062] S1-2: The volume of the ball mill is 125 mL. The filling volume of the ball mill is 37.5 mL according to the calculation formula (1). Add 10 mm ball mills to the ball mill until it reaches 37.5 mL. Then add 2 mm ball mills until the gaps between the 10 mm ball mills. The ratio of the number of 10 mm ball mills to the number of 2 mm ball mills is 3:1.

[0063] S1-3: In an inert argon atmosphere in a glove box, Li2S powder and P2S5 powder were added to a ball mill at a ball-to-material ratio of 15:1. The mixture was first mixed at 400 rpm for 20 min. Then, the mixture was ball milled at 1300 rpm for 4.5 h. Then, the mixture was ball milled at 2000 rpm for 45 min. After the ball mill was cooled, the ball mill beads were filtered out through a 200-mesh sieve and then through a 400-mesh sieve to obtain Li7P3S 11 .

[0064] S2: Preparation of solid electrolyte

[0065] S2-1: In an inert argon atmosphere in a glove box, add 1.0 g of SnF2 to 5 mL of ether solvent and disperse by ultrasonic at room temperature for 6 h to obtain a dispersion.

[0066] S2-2: In an inert argon atmosphere in a glove box, 20 g of Li7P3S prepared in step S1 was added to 11The powder was added to 40 mL of dimethyl sulfoxide, stirred at 95° C. and 1600 rpm for 5 h, and after the stirring was completed, the mixture was cooled to room temperature to obtain a viscous electrolyte slurry.

[0067] S2-3: Add the dispersion obtained in step S2-1 to the viscous electrolyte slurry obtained in step S2-2, and then stir at a speed of 1200 rpm for 5 hours to obtain a mixed slurry. After the mixed slurry is heated and evaporated to dryness, it is placed in an oven at 190°C for further drying to obtain a powder. The powder is sieved through a 200-mesh sieve to obtain a solid electrolyte.

[0068] Example 8

[0069] The solid electrolyte in this embodiment is composed of Li 10 GeP2S 12 Electrolyte and coating on Li 10 GeP2S 12 The SnF2 coating on the electrolyte surface.

[0070] The specific preparation method is as follows:

[0071] S1: Ball milling preparation of Li 10 GeP2S 12

[0072] S1-1: According to Li 10 GeP2S 12 The structural formula of Li2S and P2S 5、 GeS2 is uniformly mixed in a molar ratio of 5:1:1, wherein the amount of Li2S powder (7.82 g, 99.98%), P2S5 powder (7.55 g, 99%), and GeS2 (4.63 g, 98.94%) required to prepare 20 g of the required sulfide solid electrolyte is calculated.

[0073] S1-2: The volume of the ball mill is 125 mL. The filling volume of the ball mill is 37.5 mL according to the calculation formula (1). Add 10 mm ball mills to the ball mill until it is filled to 37.5 mL. Then add 1 mm ball mills to fill the gaps between the 10 mm ball mills. The ratio of the number of 10 mm ball mills to the number of 1 mm ball mills is 3:2.

[0074] S1-3: In an inert argon atmosphere in a glove box, Li2S powder, P2S5 powder and GeS2 powder were added to a ball mill at a ball-to-material ratio of 15:1. First, they were mixed at 500 rpm for 10 min; then, they were ball milled at 1600 rpm for 3 h; then, they were ball milled at 2200 rpm for 30 min; after the ball mill material was cooled, the ball mill beads were filtered out through a 200-mesh sieve, and then through a 400-mesh sieve to obtain Li10 GeP2S 12 .

[0075] S2: Preparation of solid electrolyte

[0076] S2-1: In an inert argon atmosphere in a glove box, add 1.0 g of SnF2 to 5 mL of ether solvent and disperse by ultrasonic at room temperature for 6 h to obtain a dispersion.

[0077] S2-2: In a glove box under inert argon, 20 g of Li prepared in step S1 was added 10 GeP2S 12 The powder was added into 50 mL of dimethyl sulfoxide, stirred at 105° C. and 1200 rpm for 7 h, and after the stirring was completed, cooled to room temperature to obtain a viscous electrolyte slurry.

[0078] S2-3: Add the dispersion obtained in step S2-1 to the viscous electrolyte slurry obtained in step S2-2, and then stir at 1600 rpm for 7 hours to obtain a mixed slurry. After the mixed slurry is heated and evaporated to dryness, it is placed in an oven at 220°C for further drying to obtain a powder. The powder is sieved through a 200-mesh sieve to obtain a solid electrolyte.

[0079] Performance Test:

[0080] 1. Test of ionic conductivity: The solid electrolyte powders prepared in Examples 1 to 8 and Comparative Example 1 were pressed into electrolyte sheets with a diameter of 16 mm as electrolyte membranes. The electrolytic cells were assembled according to the structure of SS / electrolyte membrane / SS (SS is stainless steel). Before the test, the electrolytic cell was preheated at 45°C in a constant temperature box for 12 hours to ensure that the film was in close contact with the stainless steel electrode, and then the ionic conductivity was tested by electrochemical impedance spectroscopy. The scanning range of the test was 0.01Hz to 1MHz, and the voltage amplitude was 5mV.

[0081] 2. Battery cycle performance test: The solid electrolyte powders prepared in Examples 1 to 6 and Comparative Example 1 were pressed into electrolyte sheets with a diameter of 16 mm. Assemble the solid-state battery: The positive electrode sheet is a positive electrode sheet with NCM758 as the active material, and the negative electrode is a metal lithium sheet. The specific assembly method is as follows: According to the assembly method of the button battery, take out the 2032 battery shell, place the positive electrode shell at the bottom, and then stack them in the order of positive electrode sheet-electrolyte sheet-metal lithium sheet-gasket-spring, and finally buckle the negative electrode shell to assemble into a CR2032 button battery to obtain a solid-state battery. The assembled solid-state battery was subjected to a battery cycle performance test; the test conditions were: at a temperature of 45°C and a voltage window of 1.5~3.0V, the cycle test was performed for 50 or 100 cycles at a current density of 0.3C.

[0082] The conductivity data of Examples 1 to 8 and Comparative Example 1 are shown in Table 1. It can be seen that the ionic conductivity of the uncoated Li3PS4 solid electrolyte in Comparative Example 1 is relatively low. After being coated with tin dihalide SnX2 (Examples 1-6), the ionic conductivity is significantly improved.

[0083] In Examples 1 to 3, as the amount of SnF2 coated increases, the ionic conductivity of the solid electrolyte first increases and then decreases. The ionic conductivity of the solid electrolyte prepared in Example 2 is the best.

[0084] Different tin dihalides SnX2 are used as coating layers in the solid electrolytes in Examples 2 and 4 to 6, among which tin difluoride SnF2 is used as the coating layer, which has the greatest improvement in ionic conductivity.

[0085] In Example 7 and Example 8, different sulfide solid electrolytes are coated with tin difluoride SnF2, and both have good ionic conductivity.

[0086] Table 1

[0087]

[0088] Figure 1 The cycle performance diagram of the solid-state lithium metal battery assembled in Examples 1 to 3 and Comparative Example 1 at a current density of 0.3C and a temperature of 45°C for 100 cycles shows that when the solid electrolyte in Comparative Example 1 does not contain a tin dihalide SnX2 coating layer, its first cycle discharge capacity is only 175.5 mAhg -1 After 100 cycles, the capacity dropped to 119.3 mAh g -1 The solid electrolyte in Example 1 contains a 1% tin difluoride SnF2 coating layer, and its first cycle discharge capacity is 198.2 mAh g -1 After 100 cycles, the capacity dropped to 155.6 mAh g -1 The solid electrolyte in Example 2 contains a 5% tin difluoride SnF2 coating layer, and its first cycle discharge capacity is 272.1 mAh g -1 After 100 cycles, the capacity dropped to 228.1 mAh g -1 The solid electrolyte in Example 3 contains 8% tin difluoride SnF2 coating layer, and its first cycle discharge capacity is 230.3 mAhg -1 After 100 cycles, the capacity dropped to 184.3 mAhg -1, capacity retention rate 80%. The cycle performance of the solid-state battery assembled with the solid electrolyte prepared in Examples 1 to 3 is significantly better than that in Comparative Example 1, indicating that the use of SnF2 to coat the sulfide solid electrolyte can effectively improve the electrochemical properties of the solid electrolyte. In Examples 1 to 3, as the amount of SnF2 coating increases, the cycle performance of the solid-state battery assembled with the solid electrolyte prepared therefrom increases first and then decreases. Overall, the cycle performance of the solid-state battery assembled with the solid electrolyte of Example 2 is the best, but Examples 1 and 3 also have good cycle performance.

[0089] The solid electrolyte in Example 2 contains a 5% tin difluoride SnF2 coating layer, and its first cycle discharge capacity is 272.1 mAhg -1 After 50 cycles, the capacity dropped to 241.6 mAh g -1 The solid electrolyte in Example 4 contains a 5% SnCl2 coating layer, and its first cycle discharge capacity is 220.2 mAh g -1 After 50 cycles, the capacity dropped to 187.4 mAhg -1 The solid electrolyte in Example 5 contains a 5% SnBr2 coating layer, and its first cycle discharge capacity is 246.9 mAh g -1 After 50 cycles, the capacity dropped to 199.1 mAhg -1 The solid electrolyte in Example 6 contains a 5% tin diiodide SnI2 coating layer, and its first cycle discharge capacity is 199.4 mAh g -1 After 50 cycles, the capacity dropped to 165.4 mAhg -1 , the capacity retention rate is 82.9%. When different tin dihalides SnX2 are used as coating layers, the cycle performance of the solid-state battery composed of solid electrolytes has a certain influence. When SnF2 is used as the coating layer, the cycle performance of the solid-state battery composed of it is the best.

[0090] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or additions made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that It comprises a sulfide solid electrolyte and a coating layer coated on at least part of the surface of the sulfide solid electrolyte; wherein: the coating layer is tin dihalide SnX2, and X is one or more of F, Cl, Br, and I; The preparation method of the solid electrolyte comprises the following steps: in an inert atmosphere, ultrasonically dispersing tin dihalide SnX2 in a solvent 1 to obtain a coating agent dispersion; in an inert atmosphere, adding a sulfide solid electrolyte to a solvent 2, heating and stirring to obtain an electrolyte slurry; adding the coating agent dispersion to the electrolyte slurry, stirring and mixing, heating and evaporating to dryness, and then further drying to obtain a solid electrolyte.

2. The solid electrolyte according to claim 1, characterized in that The mass of the coating layer is 1-10 wt % of the mass of the sulfide solid electrolyte.

3. The solid electrolyte according to claim 1 or 2, characterized in that The sulfide solid electrolyte is Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SiP2S 12 One of a kind.

4. The solid electrolyte according to claim 1, characterized in that The solvent 1 is diethyl ether; the concentration of tin dihalide SnX2 in the solvent 1 is 0.02-0.4 g / mL; the solvent 2 is dimethyl sulfoxide; and the concentration of the sulfide solid electrolyte in the solvent 2 is 0.4-0.7 g / mL.

5. The solid electrolyte according to claim 1, characterized in that The ultrasonic dispersion time is 4 to 6 hours; the inert atmosphere is argon atmosphere; The heating and stirring temperature is 95~105℃, the heating and stirring speed is 1200~1600rpm, and the heating and stirring time is 5~8h; The stirring speed is 1200~1600rpm, and the stirring time is 2~5h; The drying temperature is 180~220℃.

6. The solid electrolyte according to claim 1, characterized in that The preparation method of the sulfide solid electrolyte comprises the following steps: S1: Calculate the amount and proportion of raw materials according to the structural formula of sulfide solid electrolyte; S2: Calculate the filling volume of ball mill beads according to formula (1) and the volume of the ball mill jar; then add the corresponding volume of large ball mill beads into the ball mill jar to fill it to the calculated filling volume, and then add small ball mill beads to fill the gaps between the large ball mill beads; Formula (1) is: S3: Under an inert atmosphere, raw materials are added to a ball mill jar containing ball mill beads, followed by ball milling. After the ball milling is completed, the raw materials are sieved to obtain a sulfide solid electrolyte.

7. The solid electrolyte according to claim 6, characterized in that In step S1, the raw materials include Li2S and P2S5; when the sulfide solid electrolyte contains Ge, the raw materials also include GeS2; when the sulfide solid electrolyte contains Si, the raw materials also include SiS2; In step S2, the diameter of the large ball milling beads is 10 mm, and the diameter of the small ball milling beads is 1-2 mm; the number of the small ball milling beads is 1 / 3-2 / 3 of the number of the large ball milling beads.

8. The solid electrolyte according to claim 6, characterized in that In step S3, the ball milling process is specifically as follows: first, initially mix at 400-500 rpm for 10-20 min; then, ball mill at 1200-1600 rpm for 3-4.5 h; and finally, ball mill at 2000-2200 rpm for 30-45 min.

9. An all-solid-state battery, characterized in that: The electrolyte is the solid electrolyte described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Solid electrolyte with functional middle layer with gradient structure and preparation method and application of solid electrolyte

    CN116960446A